Pengaruh Pengendalian Internal, Pemanfaatan Teknologi Informasi, dan Komitmen Organisasi terhadap Kinerja Pegawai (Studi Kasus Pada Badan Perencanaan Pembangunan Daerah Provinsi Jambi) - Banjarnahor, Raffly Nataldo; Mansur, Fitrini; Hernando, Riski (Jurnal Akuntansi & Keuangan Unja, 2025)
This research aims to examine and analyze the influence of internal control, utilization of information technology, and organizational commitment on employee performance. The population in this study consisted of all 116 employees of the Regional Development Planning Agency (Bappeda) of Jambi Province. A total of 90 respondents participated in this study. Data collection was carried out using questionnaires. The data analysis technique employed in this research was a quantitative approach, utilizing statistical analysis with Outer Model Analysis, Inner Model Analysis, and Hypothesis Testing. Data processing was performed using SmartPLS (Partial Least Square) software. The results of this study indicate that Internal Control has a significant effect on Employee Performance. The Utilization of Information Technology has a significant effect on Employee Performance. Organizational Commitment does not have a significant effect on Employee Performance.